Belt and Road Initiative and the geoeconomic implications for Brazil - Rodrigues, Bernardo Salgado (2022)
In the 21st century, China has had cycles of internal and external transformations, and, from 2013 on, the Belt and Road Initiative has been playing a leading role. Concomitantly with this process, the Asian giant has approached regions such as Latin America, occupying geopolitical and geoeconomic spaces. Considering this new international context, the objective of this paper is to investigate the challenges and opportunities available to Brazil from the perspective of the country´s inclusion in this global project. This study mainly aims to confirm that institutionalized Chinese globalization would enhance trade relations, investments and supply chain financing, thus leveraging the infrastructure as well as Brazilian production and flow capacity. Using a combination of methods and aligned with the theoretical perspectives of the New Projectment Economy and of Hybrid Geoeconomics, the inclusion of Latin America in the Chinese global strategy would entail challenges for Brazil in the international scenario.